Loss of Visual Working Memory within Seconds: The Combined Use of Refreshable and Non-Refreshable Features - Ricker, Timothy J. (2010)
We re-examine the role of time in the loss of information from working memory, the limited information accessible for cognitive tasks. The controversial issue of whether working memory deteriorates over time was investigated using arrays of unconventional visual characters. Each array was followed by a post-perceptual mask, a variable retention interval (RI), and a recognition probe character. Dramatic forgetting across an unfilled RI of up to 6 s was observed. Adding a distracting task during the RI (repetition, subtraction, or parity judgment using spoken digits) lowered the level of recall, but not increasingly so across RIs. Also, arrays of English letters were not forgotten during the RI unless distracting stimuli were included, in contrast to the finding for unconventional characters. The results suggest that unconventional visual items include some features inevitably lost over time. Attention-related processing, however, assists in the retention of other features, and of English letters. We identify important constraints for working memory theories and propose that an equilibrium between forgetting and reactivation holds, but only for elements that are not inevitably lost over time.